2012
DOI: 10.3390/e14122550
|View full text |Cite
|
Sign up to set email alerts
|

Entropy Stress and Scaling of Vital Organs over Life Span Based on Allometric Laws

Abstract: Past theories on total lifetime energy expenditures and entropy generation in biological systems (BS) dealt with whole systems, but the recent literature suggests that the total metabolic rate of a BS, body (W) is a sum of product of specific metabolic rate k,m (W/kg of organ k) of each vital life organ, k {k = brain, heart, kidney and liver, or abbreviated as BHKL, and rest of the organ mass (R)} and mass of each organ k (m k ). Using this hypothesis, Kleiber's law on metabolic rate of BS ( body ) for animals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 30 publications
0
21
0
Order By: Relevance
“…It has been observed that the heat values of various nutrients expressed on kJ per kg of O 2 consumed (HHV O 2 ) is approximately constant at about 14,000 kJ/kg of O 2 [11,12]. Hence, by knowing the O 2 consumption, the amount of energy released in kJ can be readily estimated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been observed that the heat values of various nutrients expressed on kJ per kg of O 2 consumed (HHV O 2 ) is approximately constant at about 14,000 kJ/kg of O 2 [11,12]. Hence, by knowing the O 2 consumption, the amount of energy released in kJ can be readily estimated.…”
Section: Introductionmentioning
confidence: 99%
“…Biology literature defines respiratory quotient (RQ) as the ratio of moles of CO 2 produced (or CO 2 eliminated) to stoichiometric oxygen (O 2 ) moles consumed typically during oxidation reaction, for example, oxidation of nutrients in the body. The RQ factor for fat, protein, and carbohydrates-the three basic nutrients (Table 1) of the body-are 0.7, 0.8, and 1, respectively [6][7][8][9][10][11][12]. Thus, with measured CO 2 and O 2 in nasal exhaust one can determine RQ and determine which nutrient or a mixture of CH : F : P is being oxidized.…”
Section: Introductionmentioning
confidence: 99%
“…For life span metabolic energy per unit volume of mitochondria gk = z (fk − qk) in Equation (18). Previous literature provided details on conversion of allometric laws from body mass mB to organ mass k for various parameters of interest [23]. If cell density is equal to organ density, the allometric law for metabolic rate per unit mitochondrial volume in terms of vfMito,k is given as: Previous literature provided details on conversion of allometric laws from body mass m B to organ mass k for various parameters of interest [23].…”
Section: Mitochondrial Metabolic Loadingmentioning
confidence: 99%
“…Further the previous work [8,23] converted the "body mass"-based allometric relation for each organ into "organ mass"-based allometric relation:…”
Section: Smr Kmentioning
confidence: 99%
See 1 more Smart Citation